Teaching efficacy of Universiti Putra Malaysia science student teachers. - Bakar, Abd. Rahim; Konting, Mohd Majid; Jamian, Rashid; Lyndon, Novel (Project Innovation Inc, 2008)
The objective of the study was to access teaching efficacy of Universiti Putra Malaysia Science student teachers. The specific objectives were to determine teaching efficacy of Science student teachers in terms of student engagement; instructional strategies; classroom management and teaching with computers in classroom; their satisfaction with teacher education program and lastly to determine their attitudes towards teaching profession. Data were gathered using questionnaire. The sample size was 144. Findings indicate that a majority of the respondents had a high level of confident with their efficacy in term of student engagement (Mean: 3.89, S.D: 0.32), instructional strategies (Mean: 3.85, S.D: 0.33), classroom management (Mean: 3.83, S.D: 0.33) and teaching with computers in classroom (Mean: 3.89, S.D: 0.48). Pearson correlation showed that teaching efficacy and perception toward teachers education program were significantly correlated with each other (r = 0.464, p<0.05). The relationship between these two variables was positive and of moderate strength. In contrast teaching efficacy was weak and negatively correlated with attitude toward teaching profession (r = — 0.146, p< 0.05).